Kombinasi Ekstrak Etil Asetat Pegagan (Centella asiatica (L.)) dan Virgin Coconut Oil (VCO) sebagai Penyembuh Luka Bakar - Fery Indradewi Armadany; Laode Muhammad Fitrawan; Fitri Rahmadani Saputri; Vica Aspadiah; Henny Kasmawati (Journal Borneo, 2023)
Burns result from exposure to heat sources like fire, chemicals, or radiation and can lead to tissue loss or damage. Traditional healing of burns often involves using herbal remedies like gotu kola and coconut, typically oil extracts. This study aims to identify the healing effects of burns by administering a combination of ethyl acetate extract of gotu kola herb and virgin coconut oil (VCO) to mice. The mice were divided into 7 groups, namely negative control (K(-)) was given tween 20; positive control (K(+)): burn topical medicine on the market, P1: 10% Ethylacetate extract in tween 20; P2: VCO; P3: Ethyl acetate extract 10% and VCO 50% in tween 20; P4: 5% Ethyl acetate extract in VCO; P5: extract 10% Ethyl acetate in VCO and treated for 21 consecutive days with a frequency of twice a day. The results showed that the combination of 10% ethyl acetate extract of gotu kola herb in VCO exhibited the highest healing activity for burns, comparable to the positive control (K(+)) topical medicine on the market. The higher the extract concentration and VCO, the better the healing activity of burns.